Coating of cassava and yam starches in egg conservation (Research, Society and Development, 2020)
The application of coatings has been tested as a low cost technique to prolong egg shelf life. The study aimed to evaluate the use of cassava starch or yam coatings with different concentrations of plasticizer (sorbitol) on the eggs quality stored for 21 days at room temperature (25 ºC). Two experiments were carried out in which the design was completely randomized with 4 treatments and 5 replicates of 6 eggs in each treatment. Quality was assessed by weight loss, Haugh units, albumen pH, lipid oxidation and foam properties (durability index and overrun). The data were submitted to analysis of variance and their means were compared by the Dunnett and Student Newman Keuls tests at 5% probability. The presence of cassava or yam starch with 10% and 20% of sorbitol reduced weight loss, decreased Haugh unit and alcalinization of the albumen, keeping the quality close to fresh eggs. However, they did not influence lipid oxidation and foam quality. Thus, the starch coverage, regardless of sorbitol concentration, contributed to the maintenance of egg quality characteristics stored for 21 days at environment temperature (25 ºC).